Elastic properties of B, C, N-decorated on planar aluminene using density functional theory - Villagracia, Al Rey C. (Animo Repository, 2019)
This study investigated the mechanical properties of boron, nitrogen and carbon doped planar aluminene using density functional theory which was implemented through the Vienna Ab Initio Simulation package (VASP). Computations used a generalized gradient approximation (GGA) and the Perdew-Burke-Ernzerhof (PBE) exchange correlation functional. A 3x3 supercell was constructed containing a monolayer of planar aluminene with a vacuum of 20 Å above the surface. Convergence tests showed a cut-off energy of 450 eV and gamma centered grid 8 by 8 by 1 for brillouin zone sampling in the reciprocal space were enough for accurate calculations. Three possible sites of adsorption on the aluminene were identified: top, bridge and hollow sites. Static calculations were performed to estimate the location of the decorations above the aluminene surface from 0.20 Å to 6.00 Å with a step size of 0.20 angstroms. All three decorations easily be adsorbed on the surface. Results showed all decorations can be adsorbed on the surface at all sites. The in-plane bulk modulus, cohesive energy, and in-plane stiffness tensor were then calculated for all three decorations and compared to that of pristine aluminene. The modulus and stiffness of nanomaterial improved when carbon and boron are adsorbed at the bridge site, and nitrogen at the hollow site. All 2D systems in this study have better elastic properrties compared to bulk aluminum. © 2019 IEEE.